A New Blast Absorbing Sandwich Panel with Unconnected Corrugated Layers—Numerical Study - Hasan Al-Rifaie; Robert Studziński; Tomasz Gajewski; Michał Malendowski; Wojciech Sumelka; Piotr W. Sielicki (Energies, 2021)
The need for more effective defence systems is of critical importance because of the rising risk of explosive attacks. Sandwich panels are used as plastically deforming sacrificial structures, absorbing blast wave energy. To the authors’ knowledge, the blast behaviour of sandwich panels with connected (welded/bolted/riveted) corrugated layers has been well covered in literature. Hence, the aim of this numerical study was to develop new, easy-to-build, non-expensive, graded sandwich panel with ‘unconnected’ corrugated layers that can be used as a multipurpose sacrificial protective structure against wide range of blast threats. The proposed sandwich panel is composed of six unconnected aluminium (AL6063-T4) core layers encased in a steel (Weldox <semantics>460</semantics>E) frame with 330 × 330 × 150 mm overall dimensions. The numerical analysis was conducted using Abaqus/Explicit solver. First, the performance of four different nongraded layer topologies (trapezoidal, triangular, sinusoidal, and rectangular) was compared, when subjected to ~16 MPa peak reflected over-pressure (M = 0.5 kg of TNT at R = 0.5 m). Results showed that the trapezoidal topology outperformed other topologies, with uniform progressive collapse, lower reaction force, and higher plastic dissipation energy. Then, the trapezoidal topology was further analysed to design a ‘graded’ sandwich panel that can absorb a wide range of blast intensities (~4, 7, 11, 13, and 16 MPa peak reflected over-pressures) by using a (0.4, 0.8, 1.2 mm) stepwise thickness combination for the layers. In conclusion, the superior performance of the proposed sandwich panel with unconnected graded layers can be considered as a novel alternative to the conventional costly laser-welded sandwich panels. Applications of the new solution range from protecting civil structures to military facilities.